Patient considerations and targeted therapies in the management of psoriasis in Chinese patients: role of ustekinumab - Zhao, Yue (Dove Medical Press, 2014)
Psoriasis is an immune-mediated disease affecting approximately 0.1% to 0.5% of the population in the People’s Republic of China. Multiple therapeutic options are available for the treatment of moderate to severe psoriasis although they all have their respective disadvantages. The application of biological agents has brought significant efficacy in psoriasis treatment. Ustekinumab, a human monoclonal antibody targeting the interleukin-12/23 pathway, shows its superiority in efficacy, long duration of drug action, and good tolerance in patients. Phase III clinical trials of ustekinumab have been completed in Mainland China, and the drug is available in Taiwan and Hong Kong. Meanwhile, its long-term safety and efficacy merit further investigation.